Density functional response approach for electric properties of molecules - Pal, Sourav; Sophy, K. B. (International Conference on Computational Methods in Sciences and Engineering (ICCMSE 2005), 2005)
We review in this paper an implementation of the response approach to the Kohn-Sham (KS) density functional theory (DFT) for obtaining the linear and non-linear electric response properties of molecules using Gaussian type orbital basis centered on atoms. We have made a formulation in which the response of the electron density through the solution of the coupled perturbed Kohn-Sham (CPKS) equations has to be obtained only once, instead of iteratively as in the case of completely analytic procedure. Our method is based on a numerical finite-field solution of derivative KS operator, followed by analytic solution of CPKS equation. Further, using the response of the electron density, the dipole moment, polarizability and first-hyperpolarizability of the molecules are evaluated. The method is particularly useful for large systems. We tested our method using HF, BH, H2O and CO as test molecules, for which, high quality ab initio results are available. Further, our study of possible incorporation of non-dynamical electron correlation by studying BH and HF at several internuclear distances is discussed.
Keywords: Density functional theory; molecular properties; polarizability; Response approach

Density functional static dipole polarizability and first-hyperpolarizability calculations of Na-n (n=2, 4, 6, 8) clusters using an approximate CPKS method and its comparison with MP2 calculations - Sophy, K. B.; Calaminici, Patrizia; Pal, Sourav (Journal of Chemical Theory and Computation, 2007)
{We report the static dipole polarizability and first-hyperpolarizability of the sodium atom clusters, Na-n